La desnutrición y sus consecuencias en el desarrollo cognitivo infantil en el contexto Latinoamericano. - Altamirano Paredes, Diana Salomé (2024)
Childhood is an important stage in the life of a human being, the early years are fundamental for physical, emotional, and cognitive development, which will depend on factors such as adequate nutrition. The objective of the present study was to determine the consequences of malnutrition on childhood cognitive development in the Latin American context, through bibliographic research of descriptive level. The study consisted of 252 scientific articles from databases of global impact such as Dialnet, Redalyc, Pubmed, Scielo, ReserchGate, Elsevier, Medigraphic, and Google Scholar, in a period between 2014 and 2024, considering selection criteria and methodological quality, through the Critical Review - Quantitative Studies (CRF-QS) instrument, the sample was made up of 42 articles. The technique used is the bibliographic review and as instruments the bibliographic review sheet. The consequences of malnutrition in childhood cognitive development are the decrease in cognitive and intellectual processes, alteration of mental functions such as memory, attention, concentration, executive functions, reasoning, learning and language. In addition, the age with the greatest vulnerability to the consequences of malnutrition are those under 5 years of age, especially those from 0 to 3 years who are breastfeeding and complementary feeding. The consequences of malnutrition have an inversely proportional relationship with childhood cognitive development. Proper nutrition during the first years of life is essential for optimal cognitive and physical development.